Divergent evolution of T cell repertoires: extensive diversity and developmentally regulated expression of the sheep gamma delta T cell receptor. - Hein, W R (1993)
Sheep gamma delta T cells express an unprecedented repertoire of antigen receptors contributed by increased diversity in both variable and constant region gene segments. Variable region diversity results mainly from the utilization of a large family of duplicated V delta genes that have retained two distinct hypervariable segments comparable with the complementarity determining regions present in other antigen receptor V genes. This implies that sheep V delta chains have been intensely selected during evolution, probably at sites involved in ligand recognition. The sheep gamma delta heterodimer occurs in at least five isotypic variants formed by the association of a single C delta segment with one of five functional C gamma segments, each with distinctive hinge regions. Our analysis also shows that the establishment of a normal peripheral repertoire is both developmentally regulated and dependent on the continual presence of a functional thymus during ontogeny. The existence of an expanded V gene repertoire and multiple receptor isotypes together with the prominence of gamma delta T cells in the sheep immune system argues that this lineage of T cells has a more elaborate functional role in this evolutionary pathway.